Resolving Strategic Dilemmas in Ambidextrous Organizations: An Integrated Second-Order Factor Model Perspective - Cao, Rongning; Jiang, Ruchuan (Frontiers in Psychology, 2022)
Drawing on relevant literature, this study investigates the process of realizing innovation ambidexterity (IA) by proposing a theoretical model and adopting a specifically integrated mechanism with the aim to resolve strategic dilemmas in ambidextrous organizations (AOs). We analyzed a sample of 136 cross-sectional surveys collected from business managers of 132 medium- and high-tech firms in China by employing a structural equation model combined with moderation analysis to test our hypotheses. Our findings indicate that the second-order theoretical model fits the data well and AO, represented by a higher-order construct, positively affects IA. Instead of structural ambidexterity, balanced contextual ambidexterity and radical performance management can be effectively applied as the factors of the second-order construct; the design comprising balanced contextual ambidexterity and performance management is thus helpful in resolving strategic dilemmas. Our findings demonstrate that Chinese firms, as technology latecomers, are more inclined to conduct near-radical innovation. The risk of exploration crowding out exploitation efforts exists in Chinese high-tech firms. Furthermore, we provides greater insights into the moderating impact of intra-organizational practice on IA based on the fact that performance measurement balance (PMB) did not directly influence the achievement of IA and clarifies the positive role that PMB plays in improving IA.